2017
DOI: 10.1155/2017/5717968
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of MMT Clay Modified with Two Different Cationic Surfactants on the Thermal and Rheological Properties of Polypropylene Nanocomposites

Abstract: Polypropylene montmorillonite (MMT) nanocomposites were prepared by melt blending using two different organoclays modified with imidazolium and alkylammonium surfactants. The imidazolium and ammonium modified organoclays were characterized by the FTIR and SEM analysis. The effect of organic clay (MMT) on the physical properties of polypropylene was evaluated, thermal and rheological properties with different filler weight percentage. Differential scanning calorimetric results showed that imidazolium modified c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…This was related to the presence of MMT clay that created a barrier effect by hindering the formation of small molecules, thus hindering chain mobility and delaying the decomposition phase. On the other hand, MMT clay acted as an insulator for mass transportation, increasing the thermal stability of volatile products produced in the decomposition [ 166 ].…”
Section: Thermal Degradation Stability Performance Of Hybrid Natural Fiber-reinforced Biopolymer Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…This was related to the presence of MMT clay that created a barrier effect by hindering the formation of small molecules, thus hindering chain mobility and delaying the decomposition phase. On the other hand, MMT clay acted as an insulator for mass transportation, increasing the thermal stability of volatile products produced in the decomposition [ 166 ].…”
Section: Thermal Degradation Stability Performance Of Hybrid Natural Fiber-reinforced Biopolymer Compositesmentioning
confidence: 99%
“…The outcome revealed that the hybridization improved the thermal stability of the composite, with a high proportion of the MMT clay in the hybrid PLA composite producing an optimum decomposition temperature, i.e., 350 • C. This was related to the presence of MMT clay that created a barrier effect by hindering the formation of small molecules, thus hindering chain mobility and delaying the decomposition phase. On the other hand, MMT clay acted as an insulator for mass transportation, increasing the thermal stability of volatile products produced in the decomposition [166].…”
Section: Thermal Degradation Stability Performance Of Hybrid Natural Fiber-reinforced Biopolymer Compositesmentioning
confidence: 99%
“…They are laminar aluminosilicates that can enhance the stiffness and strength of the plastics through the intercalation of the polymer chains between clay galleries [ 4 ]. Most of the studies on PP/clay nanocomposites have used virgin resin, and only a few works have focused on the reinforcement of RPP where the nanofillers can potentially act as performance improvers of the degraded plastic, which has a molar mass distribution different than VPP, depending on the grade and source of the recycled polymer [ 5 , 6 , 7 , 8 ]. However, these scarce studies have only focused on the morphology and some rheological–mechanical aspects and not on the chemical safety and overall migration of the nanocomposites, which is essential for food packaging materials to guarantee human health and consumer acceptability.…”
Section: Introductionmentioning
confidence: 99%
“…The factors that hamper the reinforcement of nanostructures are alignment, dispersion of the filler and interfacial bonding between the filler and polymer [9]. Many studies reported that better mechanical properties are attributed to the formation of an interfacial adhesion layer in the presence of a bonding agent such as cationic surfactants or maleic anhydride (MAH) compatibilizer [10,11]. The simultaneous introduction of both filler and compatibilizer is beneficial, as the compatibilizers are frequently used to improve the interfacial adhesion between fillers and the matrix result in optimum dispersion which is usually difficult to Polymers 2021, 13, 1389 2 of 9 achieve [12,13].…”
Section: Introductionmentioning
confidence: 99%